"A REFLECTION ON FAMILY PLANNING AND POPULATION POLICY IN IRAN " - M Amani (Iranian Journal of Public Health, 1971)
Decision making, for establishing programs of family planning in Iran has been based on national binary census and other scattered investigations and statistic gatherings. Both national censuses have shown young population, proving a disharmony in children fertility and mortality. For executing the policy of family planning, by instituting an office of under-secretary of family planning in the Ministry of Health, a series of measures were taken. Presently, more than 1500 family planning clinics and centers are active in the country. The aim of the government is to reduce the present rate of population growth rate of 3.2 percent to 1 percent. This great aim requires an all sided actions to be taken. Meanwhile, due to interference of social and economic factors, at least time equivalent of one generation is needed for the success of this aim. With carrying out population policy, old age tendency of the population in the long term would be a problem that must be considered from now.